UTILIZATION OF AI IN MARKETING CREATIVE PRODUCTS MADE FROM WOOD WASTE IN THE CRAFTSMEN COMMUNITY OF NGEMPLAK DISTRICT, BOYOLALI REGENCY - Siswanto, Siswanto; Nughthoh Arfawi Kurdhi; Nugroho Arif Sudibyo; Supriyadi Wibowo; Putranto Hadi Utomo (Bajang Institute, 2025)
This study explores the application of Artificial Intelligence (AI) to enhance the aesthetic quality and design innovation of creative products made from wood waste in Ngemplak District, Boyolali Regency, Indonesia. Local craftsmen in this area often face challenges in improving product appearance due to limited access to design tools and technological resources. By integrating AI-based design systems, such as generative design algorithms, image enhancement models, and style transfer techniques, artisans can develop more appealing, modern, and market-responsive product designs while maintaining the authenticity of local craftsmanship. The use of AI not only supports creativity and efficiency in the product development process but also contributes to sustainability by increasing the added value of upcycled wood materials. This study highlights how AI-driven visual enhancement can bridge traditional craftsmanship with digital innovation, promoting competitiveness and sustainable growth in rural creative industries.